Corporate Debt - An Analysis Of The Influence Of Profit Margin, Liquidity And Growth On Finance-mix - Yong, Linda Lee Lin (2004)
The research project has been designed with the primary aim of analyse the influence of profit margin, liquidity and growth on the impact of leverage. More specifically, it seeks to evaluate the debt equity ratio for capital intensive industrial products industries listed on KLSE main board and second board. The study examines the financial ratios and regression equations with respect to net profit margin, current ratio and revenue growth rate. The model established from multiple regression analysis used to predict and compare with actual debt ratio of main board and second board listed industrial products companies.